Industrial Internet of things and cyber-physical systems transforming the conventional to digital - Kumar, Pardeep 1976-; Ponnusamy, Vasaki 1974-; Jain, Vishal 1983- (IGI Global, 2020)
"This book explores recent advances in the development, implementation, and business impact of IoT technologies on sustainable societal development and improved life quality"--
Description based on title screen (IGI Global, viewed 07/04/2020)
Keywords: Cooperating objects (Computer systems); Internet of things / Industrial applications